NEURONA Supplement Edition in collaboration with ASEAN Neurological Association 2025 - NEURONA (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
NEURONA, as the official scientific journal of the Indonesian Neurological Association (PERDOSNI), has been continuously published since 2007. Markinga new milestone, the journal proudly presents this supplementary edition, published in collaboration with the ASEAN Neurological Association 2025 (ASNA2025).This supplementary edition compiles 281 abstracts submitted for the meeting, encompassing a broad range of topics in neurology, including stroke,neurointervention, neuroimaging, neuro-otology and neuro-ophthalmology, neurorestoration and neuroengineering, neuroepidemiology, as well as ethicsand law.It is our earnest hope that this supplementary edition will broaden readers’ scientific perspectives and serve as a catalyst for further research andpublication in the field of neurology. We also believe that partnerships through media collaborations in neurological scientific events will help ensure thesustainability of this journal, which represents the collective effort of all neurologists in Indonesia.We extend our deepest appreciation for the continued support and collaboration that have made this publication possible